In vivo behavior of vastus lateralis muscle during dynamic performances - Finni, Taija; Ikegaw, Shigeki; Lepola, Vesa; Komi, Paavo (European journal of sport science, 2001)
Length changes in vastus lateralis fascicles were measured in vivo using ultrasonography during one-legged squat jumps (SJ), counter movement jumps (CMJ), and drop jumps (DJ) in the sledge apparatus (n = 9). Patellar tendon forces were recorded simultaneously with an optic fiber technique from 4 subjects. Fascicle length changes were compared with muscletendon unit length changes calculated from kinematic recordings. In general, the tendomuscular and fascicle length changes demonstrated similar patterns. During SJ the fascicles showed shortening throughout the action while during CMJ and DJ they underwent stretch-shortening cycle. In DJ greater muscular activity in braking phase.